Aksiologi Pendidikan Islam (Penerapan Nilai-Nilai Aqidah Dalam Pembelajaran Anak Di Mi) - Mar’atus Sholihah; Aminullah Aminullah; Fadlillah Fadlillah (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2019)
Education is a powerful tool to change the world by changing the behavior of society to be better. In Islamic education, one most important thing is the education of faith or belief, because it all starts from it. Faith is the foundation of knowledge and value. Islam emphasizes how important it is to teach values to kids in primary school level and how important is the role of parents and teachers. This method is very essential to build strong values for kids so that those values which are taught from that age would last forever. This happens because kids have powerful memory to remember everything. This paper explaines the importance of teaching values to primary school students and the best methods to instill Islamic values related to “akidah” in age 7 – 13 years old by using axiology theory and trying to relate it to philosophy. Axiology is one of philosophy study which focuses on the theory of values. Its study contains about how to reach knowledge to get values in ethic, logic and aesthetic ways. The result of this paper explaines that there are some steps which can be used for teachers in primary school to educate students about values in general and about Islamic values which most of students have the foundation before from their parents. Keywords: Islamic, education, values, primary school